(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper is intended to study parameters of consumer behaviour like perception and satisfaction on products in e-retail under wellness and fitness. This study is focused on fitness bands and apps used by consumers for their wellbeing and mindfulness. The main objective is to study consumer’s perception for wellness products and services in Mumbai. Consumer’s perception about wellness fitness bands and apps in Mumbai is also studied in brief. The study indicates that the buying perception is similar for various online wellness products and services. 180 questionnaires were collected online using convenient sampling method. The results of the study indicate that buying perception is similar for various online wellness products and services. This study also relieved that the gender as well as marital status of the customers of online wellness fitness bands and online wellness apps does not have any impact on their satisfaction level. The findings and results of this study will be helpful to strategic planners and marketing team for designing, creating and selling different types of wellness products and services on various electronic platforms.